2010
DOI: 10.3727/096368910x505864
|View full text |Cite
|
Sign up to set email alerts
|

Human Bone Marrow-Derived CD133+Cells Delivered to a Collagen Patch on Cryoinjured Rat Heart Promote Angiogenesis and Arteriogenesis

Abstract: Transplanting hematopoietic and peripheral blood-derived stem/progenitor cells can have beneficial effects in slowing the effects of heart failure. We investigated whether human bone marrow CD133+ -derived cells (BM-CD133 + cells) might be used for cell therapy of heart injury in combination with tissue engineering. We examined these cells for: 1) their in vitro capacity to be converted into cardiomyocytes (CMs), and 2) their potential for in vivo differentiation when delivered to a tissue-engineered type I co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 45 publications
(69 reference statements)
1
16
1
Order By: Relevance
“…Callegari et al (7) showed that application of a collagen sponge to a rat cryoinjury model immediately post-injury led to increased angiogenesis, compared with the control, 15 and 60 days post-implantation of the patch. Additionally, delivery of human bone marrow-derived CD133 ϩ cells (4 ϫ 10 6 cells) with a collagen scaffold increased the number of vessels in a rat cryoinjury model; however, there was no significant differentiation into cardiomyocytes (8). Similarly, application of a collagen scaffold seeded with human mesenchymal stem cells (MSCs) (1 ϫ 10 6 cells) immediately post-infarction resulted in a 30% increase in fractional shortening (FS) in the patch-treated group compared with the control in a rodent model (9).…”
Section: Cardiac Patchesmentioning
confidence: 98%
“…Callegari et al (7) showed that application of a collagen sponge to a rat cryoinjury model immediately post-injury led to increased angiogenesis, compared with the control, 15 and 60 days post-implantation of the patch. Additionally, delivery of human bone marrow-derived CD133 ϩ cells (4 ϫ 10 6 cells) with a collagen scaffold increased the number of vessels in a rat cryoinjury model; however, there was no significant differentiation into cardiomyocytes (8). Similarly, application of a collagen scaffold seeded with human mesenchymal stem cells (MSCs) (1 ϫ 10 6 cells) immediately post-infarction resulted in a 30% increase in fractional shortening (FS) in the patch-treated group compared with the control in a rodent model (9).…”
Section: Cardiac Patchesmentioning
confidence: 98%
“…HSCs can also differentiate into other specialized cell or so called plasticity such as adipocytes [1], cardiomyocytes [2], endothelial cells [3], fibroblasts/myofibroblasts [4], liver cells [5, 6], osteochondrocytes [7, 8], and pancreatic cells [9]. Most HSCs are in quiescent state within the niches that maintain HSC pool and will respond to the signals after the balance of blood cells or HSC pool is disturbed from either intrinsic or extrinsic stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Delivering stem cells with biomaterials has become an increasingly popular method, and has developed into a field of its own. Numerous studies are testing biomaterials such as injectable hydrogels or patch material from natural and synthetic sources, or growth factors as solutions for maintaining stem cells to the wound site to improve engraftment and to aid in their survival and proliferation post-transplantation [40,56,93-95]. Most of these studies are at the preclinical stage.…”
Section: Composite and Modified Biomaterialsmentioning
confidence: 99%
“…In one study, human MSCs incorporated into a collagen patch-assisted engraftment decreased left ventricle systolic interior diameter, increased anterior wall thickness and increased fractional shortening by 30% [94]. In another study, human bone marrow CD133 + -derived cells transplanted on a collagen patch onto an injured heart resulted in formation of new microvessels, thought to be induced by the patch [95]. A mixture of growth factors was able to prolong survival of transplanted cardiomyocytes derived from human embryonic stem cells, improving cell engraftment after infarct [93].…”
Section: Composite and Modified Biomaterialsmentioning
confidence: 99%